2017
DOI: 10.1002/jcph.1034
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Functional MRI in Clinical Studies for Fast and Reliable Assessment of Renal Perfusion and Quantification of Hemodynamic Effects on the Kidney

Abstract: The purpose of this study was to evaluate contrast-media-free arterial spin labeling, a technique of functional magnetic resonance imaging (MRI), for assessment of kidney perfusion in a clinical study. We examined renal perfusion by arterial spin labeling in 15 healthy adults using a clinical 1.5-T MRI system, twice under baseline conditions and 60 minutes after a single oral dose of 50 mg captopril. Data evaluation included assessment of interstudy and interrater reproducibility in addition to the pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…For example, RBF has been shown to increase during aliskiren therapy and return to original levels after withdrawal of the drug [ 36 ]. Others include telmisartan [ 28 ], furosemide [ 37 ], losartan [ 53 ] and captopril [ 54 ]. The effects of renal denervation (RDN) on RBF in a group of patients with treatment-resistant hypertension were also assessed with ASL (no changes detected up to 3 months after RDN) [ 38 ].…”
Section: Recent Developments In Renal Aslmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, RBF has been shown to increase during aliskiren therapy and return to original levels after withdrawal of the drug [ 36 ]. Others include telmisartan [ 28 ], furosemide [ 37 ], losartan [ 53 ] and captopril [ 54 ]. The effects of renal denervation (RDN) on RBF in a group of patients with treatment-resistant hypertension were also assessed with ASL (no changes detected up to 3 months after RDN) [ 38 ].…”
Section: Recent Developments In Renal Aslmentioning
confidence: 99%
“… Number of renal ASL publications in humans per year since the introduction of the technique (excluding cancer studies and conference proceedings) [ 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] ( n = 50). …”
Section: Figurementioning
confidence: 99%
“…Previous studies showed lower inter-reader reproducibility of perfusion measurements with ASL in the renal medulla than perfusion measurement in the renal cortex. [21] Last but not least, the administered dose of diclofenac is much lower than the one used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the mentioned work by Getzin et al ., a power calculation was performed for different scenarios with small pharmacological effects on renal perfusion. A sample size calculation for potential application of functional MRI in pharmacological intervention studies revealed a sample size of 6 for a mean±SD perfusion difference of 82.8 ± 56.1 ml/min/100 g (effect size 1.48) and a sample size of 17 for a perfusion difference of 41.4 ± 56.1 ml/min/100 g (effect size 0.74) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation